Application Of SQ3R Learning Model With The Help Of Wordwall Media To Improve Reading Comprehension Ability In Elementary School Students - purnomo, dedi; Nurasiah, Iis; Amalia, Arsyi Rizqia (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This research aims to describe the application of the SQ3R (Survey, Question, Read, Recite, Review) learning model with Wordwall support to improve reading comprehension skills in grade 4 elementary school students. The participants in this research were 4th grade students at SDN Rawasari Ciranjang, Cianjur Regency, West Java, consisting of 25 students. The technique used to collect data in this research is the observation method, in the form of teacher and student observation sheets and practical reading comprehension tests. This research can be said to be successful if students' reading aloud skills improve to ≥75 in classical completion or 19 students have completed the KKM (70). The research method used was classroom action research (PTK) Kemmis and Mc Taggart model research design which was carried out in two cycles. Each cycle consists of planning, implementation, action and observation, and reflection. The data analysis technique used is qualitative. Indicators for reading aloud consist of 1) determining the main idea 2) determining the meaning of words 3) ability to answer questions 4) concluding. Based on the comparative percentage of completeness of learning outcomes for each cycle, there was an increase in initial reading skills after implementing the SQ3R learning model, seen from the results of the percentage of completeness of students who met the pre-cycle KKM (70), namely 36% or 9 students, cycle I was 69% or 14 students, and cycle II was 84% or 21 students. Thus, providing action through these two cycles can improve students' reading comprehension abilities.